Possibility, Novelty, and Creativity - Haitos, Alex (Stance: an international undergraduate philosophy journal, 2019)
I am trying to develop an account of possibility that is consistent with the changing world of our experience. Possibility is often viewed as something that has the same form as actuality, minus existence. Or it is taken that what a possibility is, is a (re)combination of the elements of actuality. Neither of these views of possibility can countenance radical novelty. Using Bergson and Whitehead, I begin to construct an account of possibility compatible with genuine novelty.